Cobre e zinco no solo sob uso intensivo de dejeto líquido de suínos - Girotto, Eduardo (2007)
The main alternative of pig slurry discard is its disposition in the soil as source of nutrients for plants. However, copper and zinc accumulation in the soil has been increasing significantly and may become an environmental pollutant problem. The objective of this work was to evaluate copper and zinc potential pollutant in areas with successive applications of pig slurry through zinc and copper forms and accumulations in the soil, and their transference by surface runoff and percolation flow. The work was carried out in the experimental area of the Department of Agricultural Engineering of the Federal University of Santa Maria, Santa Maria (RS), Brazil. Typic Hapludalf soil was used and four rates of pig slurry (0, 20, 40, and 80 m3 ha-1) were applied on the soil surface presenting a total of 17 applications. In October 2006, the soil samples were collected in the depths of 0 - 2, 2 - 4, 4 - 6, 6 - 8; 8 - 10, 10 - 12, 12 - 14, 14 - 16, 16 - 18, 18 - 20, 20 - 25, 25 - 30, 30 - 35, 35 - 40, 40 - 50, and 50 - 60 cm. After collect, total contents in the pig slurry, as well as total contents and extracted contents by HCl 0.1 mol L-1 of copper and zinc in soil were analyzed. Soil samples (0 and 80 m3 ha-1 pig slurry) and dry pig slurry samples were collected and copper and zinc sequential extraction analyzed. Water volume and sediment losses were determined. Moreover, copper and zinc forms in samples of solutions transferred by surface runoff and percolation flow collected during the cycle of the corn (2006/07) in each event (rain + surface runoff) were determined. Successive applications of pig slurry increased the total content of copper and zinc extracted by HCl 0.1 mol L-1 in soil (superficial layers). These metals tended to be transferred to deeper layers of soil and to other environment compartment. The sequential extraction in soil where 80 m3 ha-1 pig slurry was applied showed an increase in the copper and zinc contents in the soil samples of the superficial layers when extracted with water deionization, MgCl2, HNO3 + H2O2, and NH2OHHCl, which represent soluble forms, exchangeable forms, mineral fraction forms, and organic matter forms, respectively. The findings showed an increase in the copper and zinc bioavailable forms. Losses by surface runoff were the main form of transferring copper and zinc, especially in treatments with successive applications of pig slurry.